2004
DOI: 10.1287/mnsc.1030.0192
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sourcing Effectiveness

Abstract: Much of the knowledge management (KM) literature focuses on ways to increase the volume of knowledge available to employees, ensure its quality, and improve its accessibility. Such supply-side arguments are limited to the extent that they do not address the demand for knowledge within organizations. This paper takes a novel approach to understanding how access to others' knowledge produces benefits by studying the extent to which individuals intentionally access each other's expertise, experience, insights, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
246
0
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(264 citation statements)
references
References 61 publications
9
246
0
9
Order By: Relevance
“…Consistent with prior findings in the knowledge sourcing literature (Gray & Meister, 2004), we find that individuals executing more demanding work (as captured by the kilolines of new code written, a common measure of complexity for a project) are more likely to source knowledge (βProject Scale = 0.1564, p<0.01). In Column 2, we add the independent variables to the model.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with prior findings in the knowledge sourcing literature (Gray & Meister, 2004), we find that individuals executing more demanding work (as captured by the kilolines of new code written, a common measure of complexity for a project) are more likely to source knowledge (βProject Scale = 0.1564, p<0.01). In Column 2, we add the independent variables to the model.…”
Section: Resultssupporting
confidence: 87%
“…A KR offers a practical solution to help people gain access to the "how-to" knowledge they would otherwise lack (Davenport & Prusak, 1998;Stein & Zwass, 1995). However, a knowledge repository cannot provide needed knowledge to inexperienced workers unless they use it (an activity sometimes referred to as knowledge sourcing (Gray & Meister, 2004)). Prior research suggests that inexperienced people may not use a KR without intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Individual propensity to learn: Borrowing from the educational psychology literature, Gray and Meister (2004) introduced the concept of individual propensity to learn into the knowledge sharing literature. They found that individuals with a strong learning orientation have strong beliefs that their ability can be improved through constant learning and adaptation.…”
Section: Control Variablesmentioning
confidence: 99%
“…cholars in marketing and strategic management argue that knowledge transfer across functional boundaries is critical for numerous outcomes, including new product success (e.g., Griffin and Hauser 1992), organizational learning (Huber 1991), and overall firm performance (e.g., Gray and Meister 2004). In the marketing literature, Menon and Varadarajan (1992) argue that a firm's market knowledge must be transferred or disseminated across departments before knowledge can play a critical role as a strategic asset.…”
mentioning
confidence: 99%